| -2x + 4| = x + 1
The above function is an absolute function
Absolute value means plus or minus
The above function can be re-written in two forms
(-2x + 4) = x + 1
Or
-(-2x + 4) = x + 1
We will solve the two equation separately
(-2x + 4) = x + 1
Open the parenthesis
-2x + 4 = x + 1
Collect the like terms
-2x - x = 1 - 4
-3x = -3
Divide both sides by -3
-3x/-3 = -3/-3
x = 1
For the second equation
-(-2x + 4) = x + 1
Open the parenthesis by multiply through with the negative sign
2x - 4 = x + 1
2x - x = 1 + 4
x = 5
The value of x is 1 and 5
x = 1 or x = 5